Constraints on Diagenetic Fluid Source and Genesis in Tight Dolostone Reservoir of Submember Ma55 of Ordovician Majiagou Formation in Northwestern Ordos Basin, China: Evidence from Petrology and Geochemistry. (18th November 2022) - Li, Baiqiang; Wu, Zhenzhen; Zhou, Taofa; Chen, Bin; Wang, Qicong; Zhang, Xiaoli
Abstract : Diagenetic fluids is one of the most important reservoir modifiers, their differences can result in various petrography, storage capacity, and geochemical characteristics, so clarifying the diagenetic fluids is vital for understanding dolostone origin. Dolomitization is an important genetic type of dolostone reservoir, the fluid properties differ in different dolomitization, which may lead to reservoir storage capacity changes. Therefore, the identification of dolomitization fluid properties is critical for deeply understanding of dolomitization process and predicting storage capacity. Two types of dolostone are developed in submember Ma55 of Majiagou Formation in northwestern Ordos Basin, with obviously different petrological characteristics and reservoir properties. On the basis of petrological studies such as core and casting thin section observation and cathodoluminescence analysis, the diagenetic fluid properties of these two dolostone are characterized by geochemical analytical methods such as major and trace element tests. The results show that Type-1 dolostone is mainly composed of micritic dolomite, showing micritic structure and algae-rich lamina structure, and accompanied by evaporite minerals and moldic pores. This type of dolostone has a various Mn content, weak to medium cathodoluminescence intensity, high contents of TiO2, Al2 O3, K2 O+Na2 O, Li, and U, and lower content of TFe2 O3 . The type-2 dolostone is composed of fine-grained dolomite with obvious residual texture of primary limestone, clear brim, and cloudy center structure, accompanied by the existence of intergranular pores. Most of this kind of dolostone have medium-strong cathodoluminescence, higher TFe2 O3 content and lower TiO2, Al2 O3, K2 O+Na2 O, Li, and U contents. Moreover, both the two types of dolostone have similar Fe/Ca and Mn/Ca ratios, and a low and concentrated CaO content, whose composition is similar to that of stoichiometric dolomite. The comprehensive analysis shows that the diagenetic fluid of Type-1 dolostone is mainly a high salinity fluid existed in plaster and calcareous sediments in a near surface environment with low temperature. The diagenetic fluid of Type-2 dolostone may be a high salinity brine formed by evaporation and concentration of seawater with normal salinity. The research results will provide a significant theoretical basis for the evaluation of dolostone reservoir quality and the prediction of favorable areas of reservoir distribution.